Larger scyphozoan species dwelling in temperate, shallow waters show higher blooming potential. (December 2021) - Fernández-Alías, Alfredo; Marcos, Concepción; Pérez-Ruzafa, Angel
Abstract: 142 scientific publications have been reviewed on the characteristics of the scyphozoans with respect to their ability to develop blooms and the most significant environmental characteristics that determine them. Special attention was paid to depth, temperature, salinity, chlorophyll concentration, and the habitat of the 39 registered blooming genera. After the review, we find that over the past decades, the number of scyphozoan blooming-species is higher than previously recorded, increasing from circa 14% to 25% of the class. Species that inhabit depths less than 27.1 m are prone to produce blooms, particularly in semienclosed areas with low rates of water renewal and high thermal amplitudes. Temperature appears as the main environmental factor controlling blooms, but food availability is essential to sustain the proliferations. Interspecies variability in the response to environmental factors observed in this work suggest that bloom predictive models should be constructed species-habitat-specific. Highlights: The updated list of blooming scyphozoan species increase from 14% to 25% of the class. While food is needed to sustain proliferations, temperature controls blooms' appearance. Shallow, semienclosed environments are more likely to host jellyfish blooms. Bloom predictive models should be species and habitat specific.